Influence of mangrove deforestation and land use change on trophic organization of fish assemblages in creek systems - Augustine W. Mwandya (African Journal of Biological Sciences, 2019)
The impacts of human related activities on trophic structure of mangrove associated fish species, was investigated by sampling fish in mangrove creeks. Trophic organization and stable isotope signatures (δ13C and δ15N) of fish in undisturbed mangrove creeks were compared with clear-cut areas of mangrove and reservoirs for saltworks and fish farms constructed after mangrove clearing. Results showed significantly higher densities, species numbers, diversity (H’) and numbers of trophic groups in undisturbed sites compared to disturbed sites. Overall, omnivorous fish comprised the most abundant feeding guild, which dominated in the cleared sites followed in order by the uncleared sites and reservoirs. The zoobenthivores/piscivores was the most diverse group, with the highest species richness in the undisturbed areas. Multivariate analysis showed that assemblage structure of omnivores in the reservoirs was separated from those in uncleared and cleared sites, while zoobenthivores/piscivores differed between uncleared sites and disturbed areas. Stable isotope ratios of δ13C and δ15N values in fish muscles indicated significant diet shifts between undisturbed and disturbed mangrove creek systems, although the effects were species-specific. The findings suggest that mangrove deforestation combined with land-use changes, has a greater impact on the trophic structure of fish in mangrove creeks than mangrove deforestation only.
Keywords: Ecology, Anthropogenic disturbance, Mangroves, Tanzania